Planning miracles : how to prevent future pandemics - Cohen, Jon, 1958- (Alfred A. Knopf, 2025)
"A groundbreaking book about the past, present, and future of pandemics, and a behind-the-scenes portrait of the groundbreaking community of scientists working tirelessly to stop the next one before it starts. In 1955, the vaccine that eliminated polio was celebrated as a "planned miracle;" today, despite the astonishing global effort that came together to develop a vaccine for COVID-19 faster than ever before, we now struggle against the rise of science denial and misinformation. Since 2020, we have had to face a terrifying truth: it's not if we'll experience another pandemic, it's when. How do we prepare to face it? Planning Miracles tells the stories of the heroes at the frontlines of epidemiology, fighting back against societal distrust and panic, monitoring the threats that exist, detecting outbreaks early, and developing new interventions as quickly as possible. Renowned science reporter Jon Cohen travels from the mountains of Vietnam to the rainforests in the Amazon, from the "wet" markets in Cambodia to fairgrounds in the United States, asking how we'll defend ourselves against the growing threat of pandemics, and finds surprising-and encouraging-answers. He meets scientists sampling bats, pigs, wild birds, and insects to hunt for the next dangerous virus. He visits labs developing next generation vaccines with cutting edge technology that aim to protect us from entire viral families. Cohen discovers the unexpected links between climate change and the spread of disease and explores efforts to improve the equitable distribution of vaccines, diagnostics, and data sharing around the world. Weaving together history, reportage, and science writing, Planning Miracles is revelatory and necessary"-- Provided by publisher.